The Influence of Psychological Factors on Consumer Purchasing Decisions in the New Normal Era with Age and Education Level as Moderating Variables - Mei Monika Asri; Roos Kities Andadari (Yayasan Riset dan Pengembangan Intelektual, 2023)
The COVID-19 pandemic has brought significant changes to consumer behavior and the retail industry. As a result, businesses need to understand the impact of psychological factors on consumer purchasing decisions in the